Improving Adolescent Mental Health Through Self-Determination Training in Coastal Areas - Veny Elita; Sri Wahyuni; Yuniar Sari, Niken; Jumaini Jumaini; Nauli, Fathra Anis; Sari, Tesha Hestyana; Fitri, Aminatul; Rustam, Murfardi; Oktavia, Deby (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2024)
ABSTRACT Background: Environmental factors, such as peers, the school environment and internet use play a major role in the mental development of adolescents. Teenagers with low self-determination are unable to determine the direction of their lives and will easily be carried away by negative influences from the environment. Objective: This community service activity is aimed at honing self-determination skills so that teenagers will be able to determine their life goals and create decision for himself. Method: Activities were carried out in the coastal area of Pekanbaru City, Riau Provine The teenagers involved were 29 teenagers in RW 11 Sri Meranti Village with an age range of 12 – 18 years. Activities are carried out in 3 stages, firstly, education about adolescent mental health. Furthermore, the teenagers were given self-determination training and independent tasks to make the personal changes they want to achieve. Results: based on the results of the training, there was an increase in participants' knowledge about adolescent mental health and self-determination scores. Impact: Teenagers are able to recognize their own potential, make short-term and long-term plans for their lives and make commitments to the changes they want to make. Keywords: Adolescent, Mental health, Self determination, Teenagers.